2019
DOI: 10.2337/dci18-0048
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Culprits in Obese Pregnancies and Gestational Diabetes Mellitus: Big Babies, Big Twists, Big Picture

Abstract: Pregnancy has been equated to a "stress test" in which placental hormones and growth factors expose a mother's predisposition toward metabolic disease, unleashing her previously occult insulin resistance (IR), mild b-cell dysfunction, and glucose and lipid surplus due to the formidable forces of pregnancy-induced IR. Although pregnancy-induced IR is intended to assure adequate nutrition to the fetus and placenta, in mothers with obesity, metabolic syndrome, or those who develop gestational diabetes mellitus, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 66 publications
1
36
0
1
Order By: Relevance
“…Potential biological mechanisms linking the association between maternal obesity and diabetes during pregnancy and growth trajectory involve “fuel‐mediated teratogenesis” that includes maternal glucose and lipids as well as amino acids . Maternal obesity per se is associated with high levels of glucose, lipids, amino acids, inflammatory changes, and insulin resistance beyond normal pregnancy and diabetes . These abnormalities in the intrauterine environment and the long‐term exposure starting from early prenatal period for the entire pregnancy may in part explain the greater effect of prepregnancy obesity or overweight on growth trajectory in offspring than diabetes or weight gain during pregnancy or postnatal breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Potential biological mechanisms linking the association between maternal obesity and diabetes during pregnancy and growth trajectory involve “fuel‐mediated teratogenesis” that includes maternal glucose and lipids as well as amino acids . Maternal obesity per se is associated with high levels of glucose, lipids, amino acids, inflammatory changes, and insulin resistance beyond normal pregnancy and diabetes . These abnormalities in the intrauterine environment and the long‐term exposure starting from early prenatal period for the entire pregnancy may in part explain the greater effect of prepregnancy obesity or overweight on growth trajectory in offspring than diabetes or weight gain during pregnancy or postnatal breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, studies have reported a causal link between maternal smoking and subsequent increased risk of insulin resistance, type 2 diabetes, and hypertension, although the evidence here is weaker than that for overweight/obesity [64]. At the other end of the spectrum, intrauterine exposure to hyperglycemia and/or maternal obesity also increases the risk of later life obesity and impaired glucose tolerance [22, 65, 66]. A recent study describes how intrauterine exposure to hyperglycemia affects the offspring in a sex-specific way, with females being more prone to the effects [67].…”
Section: The Influence Of Early Life Environment On Later Life Inmentioning
confidence: 98%
“…The hPGH may also have the same diabetogenic effects as pituitary growth hormone such as hyperinsulinemia, decreased insulin-stimulated glucose uptake and glycogen synthesis, and impairment of the ability of insulin to suppress hepatic gluconeogenesis. Some of these effects have been demonstrated in rodents in vitro [22], whereas the effects during human pregnancy are less evident [23]. It appears that hPGH is the driver of the levels of insulin-like growth factors (IGFs) during pregnancy [24, 25], thereby indicating an interplay between GH, hPGH, IGFs, and insulin-like growth factors binding proteins (IGF-BPs), which might be the pathway coupling insulin resistance and the growth hormone axis during pregnancy.…”
Section: Hormonesmentioning
confidence: 99%
“…Finally, while many gaps remain in the current state of knowledge, techno-logical advancements are likely to be a key driver of developments in this space. Indeed, contributions from fields such as metabolomics are already shedding light on the mechanisms underlying GDM[50]. Analytical techniques such as mass spectrometry and nuclear magnetic resonance spectroscopy have been employed to investigate metabolic profiles associated with GDM and hence determine the pathways leading to insulin resistance[50].…”
Section: Gdm Nutritional Guidelinesmentioning
confidence: 99%
“…Indeed, contributions from fields such as metabolomics are already shedding light on the mechanisms underlying GDM[50]. Analytical techniques such as mass spectrometry and nuclear magnetic resonance spectroscopy have been employed to investigate metabolic profiles associated with GDM and hence determine the pathways leading to insulin resistance[50]. Lipid and amino acid molecules have been most consistently identified by these processes thus far[51].…”
Section: Gdm Nutritional Guidelinesmentioning
confidence: 99%